Effect of immobilization stress on gene expression of catecholamine biosynthetic enzymes in heart auricles of socially isolated rats - Gavrilovic,L. (2009)
Chronic stress is associated with the development of cardiovascular diseases. The sympathoneural system plays an important role in the regulation of cardiac function both in health and disease. In the present study, the changes in gene expression of the catecholamine biosynthetic enzymes tyrosine hydroxylase (TH), dopamine-β-hydroxylase (DBH) and phenylethanolamine N-methyltransferase (PNMT) and protein levels in the right and left heart auricles of naive control and long-term (12 weeks) socially isolated rats were investigated by Taqman RT-PCR and Western blot analysis. The response of these animals to additional immobilization stress (2 h) was also examined. Long-term social isolation produced a decrease in TH mRNA level in left auricles (about 70%) compared to the corresponding control. Expression of the DBH gene was markedly decreased both in the right (about 62%) and left (about 81%) auricles compared to the corresponding control, group-maintained rats, whereas PNMT mRNA levels remained unchanged. Exposure of group-housed rats to acute immobilization for 2 h led to a significant increase of mRNA levels of TH (about 267%), DBH (about 37%) and PNMT (about 60%) only in the right auricles. Additional 2-h immobilization of individually housed rats did not affect gene expression of these enzymes in either the right or left auricle. Protein levels of TH, DBH and PNMT in left and right heart auricles were unchanged either in both individually housed and immobilized rats. The unchanged mRNA levels of the enzymes examined after short-term immobilization suggest that the catecholaminergic system of the heart auricles of animals previously exposed to chronic psychosocial stress was adapted to maintain appropriate cardiovascular homeostasis.